COVID‐19 in Western Australia: 'The last straw' and hopes for a 'new normal' for parents of children with long‐term conditions - Stephanie Smith; Mary Tallon; James Smith; Lauren Jones; Evalotte Mörelius (Wiley, 2023)
Abstract Background Children with long‐term conditions are vulnerable due to the treatments required for their conditions. Since the start of the coronavirus disease 2019 (COVID‐19) pandemic, Western Australians experienced restrictions that changed daily life activities but were able to return to some of their previous routines due to the restrictions. Aim The study explored the stress experiences of parents caring for children with long‐term conditions during COVID‐19 in Western Australia. Design and Participants The study was codesigned with a parent representative caring for children with long‐term conditions to ensure essential questions were targeted. Twelve parents of children with various long‐term conditions were recruited. Ten parents completed the qualitative proforma, and two parents were interviewed in November 2020. Interviews were audio‐recorded and transcribed verbatim. Data were anonymised and analysed using reflexive thematic analysis. Findings Two themes were produced: (1) 'Keep my child safe' describes the children's vulnerabilities due to their long‐term conditions, the adjustments parents' made to keep their children safe and the various consequences faced. (2) 'COVID‐19's silver lining' covers the positives of the COVID‐19 pandemic, including their children having fewer infections, the availability of telehealth appointments, relationship improvements and the parent's hopes for a new normal where behaviours prevent transmission of infectious (e.g., hand sanitising). Conclusion Western Australia provided a unique context for the COVID‐19 pandemic due to no transmission of the virus severe acute respiratory syndrome coronavirus 2 at the time of the study. The tend and befriend theory aids in explaining the parents' stress experiences, and the application highlights a unique aspect of this theory. Parents tended to their children during COVID‐19, but many could no longer rely on others for connection, support and respite, and became further isolated in attempting to protect their children due to COVID‐19 consequences. The findings highlight that some parents of children with long‐term conditions need specific attention during times of pandemics. Further review is recommended to support parents through the impact of COVID‐19 and similar crises. Patient or Public Contribution This study was codesigned with an experienced parent representative who was part of the research team and involved throughout the research process to ensure meaningful end‐user engagement and ensure essential questions and priorities were addressed.